Parenting and mobile phone addiction tendency of Chinese adolescents: The roles of self-control and future time perspective - Peng, Yuan; Wang, Yali; Liu, Shaozhuo; Hu, Xingzhao (Frontiers in Psychology, 2022)
Previous studies have examined the impact of parenting on adolescents’ mobile phone addiction tendency. However, relatively few studies examine the potential mechanism underlying such a relationship. Thus, the present study further explored the mediation effect of self-control and the moderating effect of future time perspective between parenting and Chinese adolescents’ mobile phone addiction tendency. A sample of 1349 Chinese adolescents (Mage = 15. 22 years, SD = 0.79) responded to the anonymous questionnaires regarding parenting including parental control and parental care, self-control, future time perspective, and mobile phone addiction tendency. Results showed that: (1) parental control was positively related to adolescents’ mobile phone addiction tendency, while parental care was negatively related to adolescents’ mobile phone addiction tendency; (2) self-control could mediate the pathway from both parental control and parental care to adolescents’ mobile phone addiction tendency; (3) The indirect pathway could be moderated by future time perspective. Specifically, a high future time perspective combined with high self-control predicted a low level of mobile phone addiction tendency. In contrast, low self-control was associated with high mobile phone addiction tendency, whatever their future time perspective. The present study revealed a complex interplay between family and individual factors contributing to adolescents’ mobile phone addiction tendency.